Mid- to Long-Term Outcome after Arthroscopy and Proximal Abducting Ulnar Osteotomy Versus Arthroscopy Alone in Dogs with Medial Compartment Disease: Thirty Cases - Coghill, Fiona J.; Ho-Eckart, Louisa K.; Baltzer, Wendy I. (Veterinary and Comparative Orthopaedics and Traumatology, 2020)
Objective The aim of this study was to determine owner-assessed mid- to long-term outcome for dogs with medial compartment disease treated arthroscopically with fragment removal with or without proximal abducting ulnar osteotomy (PAUL).Study Design This was a retrospective clinical study.Materials and Methods Records from 30 dogs with medial compartment disease treated with arthroscopy with or without PAUL were retrospectively reviewed over a 5-year period. Proximal abducting ulnar osteotomy cases were matched to arthroscopy-alone controls based on bodyweight and modified Outerbridge score. Outcome was assessed via owner questionnaire using the Canine Brief Pain Inventory (CBPI), frequency of non-steroidal anti-inflammatory drug (NSAID) administration and owner-assessed overall improvement.Results Canine Brief Pain Inventory score for dogs in the PAUL group was not significantly different from the control group (p = 0.54). Non-steroidal anti-inflammatory drug administration was similar between groups (p = 0.61) and there was no significant difference between modified Outerbridge score and outcome (p = 0.57) over a median of 43 months post-surgically (range: 7–66 months). Canine Brief Pain Inventory and NSAID use were affected by the age of the dog with dogs greater than 3 years of age at the time of surgery having a higher CBPI score and increased NSAID use regardless of the surgery that was performed. Overall, owner-assessed improvement was not different between groups (p = 0.72).Clinical Significance Proximal abducting ulnar osteotomy showed no owner-assessed benefit over arthroscopic medial coronoid fragment removal for dogs with medial compartment disease and modified Outerbridge score of 3 or greater. A prospective, blinded, controlled clinical trial is warranted to determine the appropriate clinical application of the PAUL procedure.
Keywords: medial compartment disease; elbow dysplasia; proximal abducting ulnar osteotomy; arthroscopy; dogs